A colorimetric hydroxy naphthol blue based loop-mediated isothermal amplification detection assay targeting the β-tubulin locus of Sarocladium oryzae infecting rice seed - Logeshwari, R.; Gopalakrishnan, C.; Kamalakannan, A.; Ramalingam, J.; Saraswathi, R. (Frontiers in Plant Science, 2022)
Sarocladium oryzae is a widely prevalent seed-borne pathogen of rice. The development of a rapid and on-site detection method for S. oryzae is therefore important to ensure the health of rice seeds. Loop-mediated isothermal amplification (LAMP) is ideal for field-level diagnosis since it offers quick, high-specific amplification of target template sequences at a single temperature. We designed primers based on the β-tubulin region of S. oryzae. The LAMP technique devised was extremely sensitive, detecting the presence of the S. oryzae template at concentrations as low as 10 fg in 30 minutes at 65°C. The assay specificity was confirmed by performing the experiment with genomic DNA isolated from 22 different phytopathogens. Through the addition of hydroxy naphthol blue in the reaction process prior to amplification, a colour shift from violet to deep sky blue was seen in the vicinity of the target pathogen only. Finally, the LAMP assay was validated using live infected tissues, weeds and different varieties of seeds collected from different locations in Tamil Nadu, India. If developed into a detection kit, the LAMP assay developed in this study has potential applications in seed health laboratories, plant quarantine stations, and on-site diagnosis of S. oryzae in seeds and plants.